The Effect Of Acidic Refractory Materials In Electric Furnaces On The Quality Of Molten Metal (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article analyzes the wear of the refractory lining in an induction furnace by considering the thermal conductivity and oxidation level of the internal refractory materials, as well as the addition of various fluxes and ferroalloys to the molten alloy. The study also evaluates how the temperature of the melt influences the rate of lining erosion
Keywords: induction furnace; alloy; lining; refractory brick